Cytomorphological alterations of thyroid gland consequent upon fluorosis - Chaluvadi, Jwalaram Kumar; Kande, Srinivasulu; Ramalinga, Viswa Kumar; Kutala, Vijay Kumar; J., Vijay Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Study aimed at assessing the impact of elevated fluoride from drinking water on thyroid gland structure and function in fluorosis prone areas. Iodine is incorporated in the thyroid synthesis by thyroid gland but in the presence of low Iodine levels fluoride is likely to interfere with the concentrating capacity of thyroid of iodine in thyroid production, consequently reflecting changes in thyroid parameters and also cytomorphological features manifesting hypothyroidism in association with different pathological entities. Methods: Prakasam district in Andhra Pradesh is fluorosis prone zone and subjects are picked up from highly vulnerable zone in this district and their specimens are collected to study cytomorphological changes of the thyroid gland and biochemical parameters of blood samples for thyroid function test were considered. Cytological study by way of Fine Needle Aspiration Cytology (FNAC) of thyroid gland, biochemical parameters pertaining to function of thyroid gland namely Free triiodothyronine (FT3), Free Thyroxine (FT4) and Thyroid stimulating hormone (TSH) were assessed in the subjects from fluorosis prone zone. Results: The results were statistically significant with concurrent association of different cytological alterations of thyroid gland in these subjects like Hashimoto’s thyroiditis of hypothyroidism, adenomatous goitre, colloid goitre and few of follicular adenoma/neoplasm. FNAC makes cytological changes evident showing different morphological features that comprise different pathological entities largely with an evidence of hypothyroidism in most of the cases in the given study. Conclusions: The results of the study strongly suggest assessing the magnitude of the problem of fluorosis and also magnitude of its influence on thyroid structure and function that warrants assessment of the thyroid function by biochemical and cytological studies.